IMPLEMENTING MULTILITERACIES PEDAGOGY TO FOSTER STUDENTS' MULTIMODAL LITERACY IN A TECHNOLOGY-SUPPORTED ESP COURSE: A CASE STUDY IN AN INDONESIA POLYTECHNIC CLASSROOM - Siti Kustini, - (2021)
The rapid changes of information and communication technologies bring new literacy landscape which requires teachers to realign, reconceptualize, and reform their pedagogical frameworks to assist learners to acquire knowledge and skills in handling and transforming knowledge and information gained from these multimodal resources and apply that knowledge in their social contexts. In the context of English language education, multiliteracies pedagogy was offered as a promising solution to bring in line with these educational demands. This study attempts to explore the potentials of multiliteracies approach in developing students' multimodal literacy in an English for Specific Purposes (ESP) classroom in a higher vocational education in Banjarmasin. The theoretical construct of multiliteracies was deployed as the basis for setting up the pedagogical practices in that the instructional procedures carried out in the classroom strictly adhere to the principles of this theory. To obtain a detailed and comprehensive account of the implemented teaching program, a qualitative case study design was applied. The participants of this study were 30 semester two students of Informatics Engineering taking English as their compulsory subject. To establish trustworthiness of the research results, multiple sources of data collections were utilized including classroom observations, semi-structured interviews, open-ended questionnaires, students' written reflections, and students' artefacts. The data gained from these research instruments were qualitatively analyzed through thematic and categorical coding. The findings of this study suggest that multiliteracies pedagogy helped ESP learners to develop multimodal literacy in several ways. Firstly, despite the challenges encountered during the implementation, the multiliteracies teaching program to some extent was able to elevate students' competences in viewing (observing and comprehending) and composing multimodal texts and disseminating those texts publicly through digital media. Secondly, students in varying degree had the ability to recognize and orchestrate design elements of multimodal texts that include words (linguistic mode), visual and moving images (non-linguistic mode). In terms of linguistic mode, students were likely able to produce comprehensible sentences and articulate their ideas in a logical manner regardless their inappropriate selections of lexical terms and inaccuracy of grammar usage. In terms of non-linguistic mode, students were able to demonstrate their understanding of the typical functions that each mode serves. Lastly, the enactment of multiliteracies pedagogy could likely empower students to be creative and independent in their ESP learning. In respect to students' perceptions, the multiliteracies teaching program was perceived to be very engaging and motivating and able to improve their English competence and digital skills. This study informs that the multiliteracies pedagogy is a powerful pedagogy to be implemented in ESP context and in that implementing this pedagogy is timely for learners who are nowadays surrounded by a technology-saturated and an image-rich environment.